The synergistic effect of cation mixing in mesoporous BixFe1−xVO4 heterojunction photoanodes for solar water splitting - Zhang, Mengyuan (2019)
Mixed metal vanadates are an interesting class of materials due to their favorable bandgap for visible light absorption and their catalytic activity. Here, we report a novel BixFe1−xVO4 mixture system fabricated by electrospinning, which upon annealing is composed of triclinic FeVO4 and monoclinic BiVO4 phases. The mixture demonstrates extended optical absorption and a clear bandgap shift as compared with a pure BiVO4. This is also accompanied by an extended wavelength range for its photoactivity as evident from the incident photon-to-current efficiency. In addition, the mixture with a Bi/(Bi + Fe) ratio of 0.5 (i.e., x = 0.5) shows superior charge transfer and charge separation efficiency. The improved charge transfer efficiency is attributed to the higher catalytic activity of the mixed cation, while the presence of a BiVO4/FeVO4 heterojunction enhances the charge separation. The formation of the heterojunction is verified through detailed microscopic investigations revealing BiVO4 particles intimately surrounded by FeVO4. Our results demonstrate the advantage of establishing a mixture of complex metal oxides in extending optical absorption and boosting the photoelectrochemical performance.